An aryne-based route to substituted benzoisothiazoles - Chen, Y; Willis, MC (American Chemical Society, 2015)
The combination of arynes, generated using fluoride from the corresponding 2-(trimethylsilyl)aryl triflates, and 3-hydroxy-4-aminothiadiazoles leads to the selective formation of 3-amino-substituted benzo[d]isothiazoles. Variation of the substitution pattern of the aryne precursor, and of the thiadiazole, is possible, with the target heterocycles being obtained in good to excellent yields. In all cases, use of 3-hydroxy-4-aminothiadiazoles leads to incorporation of the amino-substituent in the product heterocycle.